Evaluasi Kompetensi Profesional Guru IPS pada MTs di Kecamatan Mranggen Kabupaten Demak - Sofyani . (Jurnal Edutrained : Jurnal Pendidikan dan Pelatihan, 2021)
Abstrak This study seeks to determine the professional competence of social studies teachers and how individual background factors affect professional competence. This research is a type of evaluation research, using the Benchmarking evaluation model, in which the results obtained will be compared with the professional competency standards of teachers prevailing in Indonesia. The study population was all social studies teachers at MTs in Mranggen District, amounting to 31 people. The data analysis technique used is quantitative analysis. The data analysis step of this research is descriptive data analysis and regression test. The results showed that 32.2% of the teachers had professional competence in the very good category, 25.8% in the good category, and 34.4% in the sufficient category. The regression results show that there is an effect of individual teacher factors on the formation of the professional competence of social studies teachers at MTs in Mranggen District. Teaching experience has the greatest influence in the formation of teacher professional competence, namely 44.63%, then the work environment is 31.16%, educational background is 25.80% and training experience is 0.35%.